A Study on Drilling of AISI 304L Stainless Steel with Nanocomposite-Coated Drill Tools - Uysal, Alper (SPRINGER HEIDELBERG, 2014)
Stainless steels are considered to be difficult to machine due to specific properties such as high toughness, work-hardening, and low heat conductivity. Built-up edge and irregular wear situations are often faced in the machining of stainless steel parts. In addition, various problems such as low surface roughness and breakage of drill tool occurred in the drilling of these materials. In this study, nanocomposite-coated and uncoated Tungsten Carbide (WC) tools were compared to specify the performance of nanocomposite coating in the drilling of AISI 304L stainless steel workpieces. The breakages and damages of nanocomposite-coated and uncoated WC drill tools were presented when the stainless steel parts were drilled. Drill tool tip damages were investigated by microscope, and surface roughness values of the drilled holes were measured. -coated WC drill tools were less damaged than uncoated WC drill tools due to the fact that coating reduced the drill tool-workpiece friction and increased the wear resistance. The surface roughness of the drilled holes with -coated WC drill tools was better than that of the drilled holes with the uncoated WC drill tools.
Keywords: AISI 304L stainless steel; Drill tool damage; nACo (R) coating; Surface roughness; CEMENTED CARBIDE TOOLS; WEAR; PARAMETERS; Science & Technology - Other Topics